Behavioral Aspects of Operational Cost Control to Increase Profits in "X" - Santi Prameswari; Sri Trisnaningsih (Formosa Journal of Multidisciplinary Research, 2024)
In running a business owned by an individual, it can be said to be successful if after a certain period of time the business experiences an increase in capital, profits or management in controlling costs. This research aims to find out whether controlling operational costs can increase profits at Tegoeh Djaja Konveksi Screen Printing. This research is a type of qualitative descriptive research, primary data obtained through interviews and literature review. The research method used in this research is a qualitative method, namely describing or describing the research results according to the conditions that occurred at the Tegoeh Djaja Konveksi Screen Printing. The research results obtained show that controlling operational costs cannot efficiently increase profits at Tegoeh Djaja Konveksi Screen Printing.